Short Interfering RNA Directed against the SLUG Gene Increases Cell Death Induction in Human Melanoma Cell Lines Exposed to Cisplatin and Fotemustine - Ivan Vannini; Massimiliano Bonafe; Anna Tesei; Marco Rosetti; Francesco Fabbri; Gianluca Storci; Paola Ulivi; Giovanni Brigliadori; Dino Amadori; Wainer Zoli (Cellular Oncology)
Background: Melanoma remains largely resistant to currently available chemotherapy, and new strategies have been proposed to flank standardized therapeutic protocols in an effort to improve efficacy. Such an approach requires good knowledge of the mechanisms involved in the resistance and survival of melanoma cells. In this context, the SLUG gene has recently been characterized as a major regulator of melanocytes and melanoma cell survival. Methods: We tested the hypothesis that an oligonucleotide-based short interfering RNA (siRNA) directed against the SLUG gene increases the susceptibility of melanoma cells to drugs such as cisplatin and fotemustine, which are frequently used to treat this cancer. Results: It was found that SLUG siRNA increased cisplatin-induced cell death and rendered the drug active in vitro at half its plasmatic peak concentration. Such activity was correlated with an upregulation of the pro-apoptotic gene, PUMA. Furthermore, SLUG siRNA increased the capacity of fotemustine to elicit cell death and induced p21WAF1 upregulation, resulting in cell cycle arrest. Interestingly, this pathway did not require functional p53. Conclusion: These findings suggest that SLUG siRNA enhances the efficacy of two of the most widely used drugs to treat melanoma.